FAKTOR-FAKTOR YANG MEMPENGARUHI STATUS KELULUSAN BERDASARKAN JALUR MASUK MAHASISWA DENGAN MODEL REGRESI LOGISTIK BINER BIVARIAT (Studi Kasus Mahasiswa FSM Universitas Diponegoro) - Safitri Daruyani; Yuciana Wilandari; Hasbi Yasin (Department of Statistics, Faculty of Science and Mathematics, Universitas Diponegoro, 2013)
The acceptance of college students in public universities are divided into two ways, the National Selection of Public University Entrance by invitation and the National Selection of Public University Entrance by non invitation. The National Selection of Public University Entrance by invitation is a way to get candidate students from The Senior High Schools that have good achievement, where as the other one open wider access. Nevertheless, the college students who enter through the invitation or non invitation, they don’t necessarily have a better academic achievement or worse than each other. After through the learning process in college, the success of the students are marked with their academic achievement that shown by the index of academic achievement, that if they pass expressed by the status of graduation, cumlaude or not cumlaude. To find out the factors that affect the status of student graduation based on the entrance, the regretion model that can be used is bivariate biner logistic regretion, because it consist of two response variable, the status of graduation and the entrance of the college students. Maximum likelihood estimation is used to estimate the parameter model. To examine the significance of the parameter use Likelihood ratio test and Wald test. Major option and live adress are the significance variables that affect the status of graduation based on the entrance of the college student from predictor variable partially test of school report grades, national test grades, major option, live adress, study method, live cost, students’ relationship with friends and family,and study motivation. Whole test and individual test indicate that major option variable affect the status of graduation based on the entrance significantly.